2016
DOI: 10.1097/pcc.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA-208a, -208b, and -499 as Biomarkers for Myocardial Damage After Cardiac Surgery in Children

Abstract: Circulating micro-RNA-208a, -208b, and -499 are detectable in the plasma of children undergoing cardiac surgery and may serve as novel biomarkers for monitoring and forecasting postoperative myocardial injury and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…With regard to specific postoperative complications, only a few studies addressing miRNAs as possible biomarkers are available so far: for example, a study investigating 30 children after heart surgery revealed a set of 3 miRNAs (208a, 208b, and 499) as possible biomarkers for early detection of postoperative myocardial damage. 110 Also, miRNA-499 was identified as a marker for postoperative MI in 30 patients undergoing coronary artery bypass grafting. 111 Several ongoing studies are evaluating the suitability of miRNAs as biomarkers in postoperative care, for example, as predictors of postoperative delirium (ClinicalTrials.gov).…”
Section: Mirnas In Anesthesia and Postoperative Carementioning
confidence: 99%
“…With regard to specific postoperative complications, only a few studies addressing miRNAs as possible biomarkers are available so far: for example, a study investigating 30 children after heart surgery revealed a set of 3 miRNAs (208a, 208b, and 499) as possible biomarkers for early detection of postoperative myocardial damage. 110 Also, miRNA-499 was identified as a marker for postoperative MI in 30 patients undergoing coronary artery bypass grafting. 111 Several ongoing studies are evaluating the suitability of miRNAs as biomarkers in postoperative care, for example, as predictors of postoperative delirium (ClinicalTrials.gov).…”
Section: Mirnas In Anesthesia and Postoperative Carementioning
confidence: 99%
“…In a study by Bolkier et al, the plasma levels of some cardiac-associated miRNA were dramatically increased after surgery of children undergoing open-heart surgery for CHDs. The increase in the selected miRNAs (microRNA-208a, -208b and -499) correlated with higher troponin levels and delayed hospital discharge [65]. This evidence further justifies the use of circulating miRNAs as biomarkers not only for the diagnosis but also for prognosis and prediction of surgical clinical outcome.…”
Section: Reoxygenation and Reperfusion Injuriesmentioning
confidence: 86%
“…Contrary to the levels of miR-133 and miR-499, the level of miR-208 positively correlated with cardiac biomarker CK-MB and may be more relevant to cardiac failure, because muscle injures influence the expression of the other two miRNAs [ 88 ]. MiR-208 and miR-499 appear to be promising as factors of myocardial damage after cardiac surgery not only in adults but also in children [ 155 ].…”
Section: Perioperative Prognostic Value Of Mirnasmentioning
confidence: 99%